The influence of natural feeding on human health: short- and long-term perspectives - Grzelak, Teresa; Woźniak, Urszula; Czyżewska, Krystyna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Breastfeeding is the most appropriate way to nourish infants. It promotes proper physical and intellectual development of the child. Human milk is unique and impossible to replicate with any other kind of food. However, using maternal milk not only has beneficial effects on the infant’s health but it can also help to prevent illnesses in adulthood. Breastfeeding improves immunity and consequently decreases the occurrence of infections, especially those of the gastrointestinal tract and respiratory tract. Moreover, it helps to reduce the risk of some disorders such as allergies, diabetes mellitus type 1, obesity and arterial hypertension.